Respuesta :

Answer:

For this equation the answer is : [tex]x=\frac{1}{8}[/tex]

Step-by-step explanation:

Firstly, We'll have to take the LCM of the denominators as usual.

Here, The deniominators are : [tex]2[/tex] and [tex]3.[/tex]

LCM = [tex]2 × 3 = 6[/tex]

Now we can solve our equation:

[tex]\frac{3(2x-1)}{6} -\frac{2(x-5)}{6} =\frac{5}{4}[/tex]

[tex]\frac{(6x-3)-(2x-10)}{6} =\frac{5}{4}[/tex]

[tex]\frac{4x+7}{6} = \frac{5}{4}[/tex]

[tex]4x+7=7.5[/tex]

[tex]4x=\frac{1}{2}[/tex]

[tex]x=\frac{1}{8}[/tex]